On Buckling of Cylindrical Shells Under Combined Loading - Gheisari, M.; Nezamabadi, A.; Khazaeinejad, P. (Journal of Advanced Manufacturing Technology (JAMT), 2017)
This paper presented an analytical investigation of the buckling behavior of cylindrical shells under a combined action of thermal and mechanical loadings based on the general form of Green’s strain tensor in curvilinear coordinates. While the shell was subjected to lateral pressure, it was assumed to be under either a uniform temperature increase or a uniform temperature gradient. A dimensionless load interaction parameter was considered to express the ratio of thermal and mechanical loads. The system of governing equations was derived using the harmonic series and was optimized with respect to harmonic numbers to find the critical buckling loads of the cylindrical shells. Results were calculated for both the Donnell and Green-types of kinematic nonlinearity. Comparison studies showed that both types of kinematic nonlinearity predicted the same critical buckling loads for thin cylindrical shells whereas for moderately thick cylindrical shells, the latter type of kinematic nonlinearity predicted higher critical buckling loads than the former type of kinematic nonlinearity.